Mechanism of late failure of the Alvarez disc valve prosthesis. Issue 5 (May 1985) - Gibbs, J L; Davies, G A; Schofield, A; Wharton, G A; Watson, D A; Gerlis, L M
Abstract : An Alvarez disc valve prosthesis had been implanted in the mitral and tricuspid positions in 15 patients between 1964 and 1967 in this hospital. Of these 15 patients, only three survived longer than 10 years, all three dying unexpectedly between 16 and 18 years postoperatively. Two deaths were a direct result of disruption of the Alvarez prosthesis. The third patient was not examined at necropsy, but in retrospect the history was highly suggestive of valve malfunction. Cross sectional and pulsed Doppler echocardiography made valuable contributions to the diagnosis in both cases of valve disruption and, when available, should be part of the primary investigation of suspected prosthetic heart valve failure. The Alvarez valve prosthesis is liable to erosive wear which may cause late detachment of the disc from the valve ring with abrupt and catastrophic haemodynamic consequences.